“Good sense” in the twenty-fifirst century - Jackson, Robert P. (International Gramsci Journal, 2023)
This is the abstract of a review in English by Robert P. Jackson of the book by Kate Crehan, Gramsci’s Common Sense. Inequality and its Narratives (Durham, Duke University Press 2016).